Basic Repairs and Maintenance for Home Landscape Irrigation Systems - Mary S. McCready; Michael D. Dukes; Kati Migliaccio (EDIS)
AE451, a 7-page illustrated fact sheet by Mary S. McCready, Michael D. Dukes, and Kati Migliaccio, instructs homeowners in how to detect and repair some basic problems of automatic irrigation systems — clogged sprinklers, sprinkler and valve leaks, obstructed sprinklers, overspray, missing nozzles, and design problems. Published by the UF Department of Agricultural and Biological Engineering, September 2009. Revised October 2009.